The Influence of Product Reviews and Ratings and Shopee Live on Purchase Decisions through Consumer Trust as an Intervening Variable on Shopee - Prabowo, Ibnu Tri; Purnamasari, Pupung (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This study aims to examine the influence of product reviews and ratings and Shopee Live on consumer purchase decisions on the Shopee e-commerce platform, with consumer trust as an intervening variable. Along with the rapid development of e-commerce in Indonesia, platforms such as Shopee have offered various features to improve the shopping experience, including product reviews, ratings, and live streaming features such as Shopee Live. Product reviews and ratings are often important indicators for consumers in making purchase decisions, as they provide social proof that increases consumer confidence in the quality of the products sold. Meanwhile, Shopee Live allows for direct interaction between sellers and buyers, which can reduce uncertainty in online shopping, as well as strengthen consumers' emotional connection and trust in products and sellers. This study uses a quantitative method with a survey design to collect data from Shopee consumers who actively use the Shopee Live feature and often buy products on the platform. The collected data was then analyzed using Smart PLS version 4, a software for Partial Least Squares (PLS), which allows testing the relationship between the variables involved. The results of the analysis show that product reviews and ratings have a significant positive influence on consumer trust, as well as Shopee Live, which has also been proven to increase consumer trust. Consumer trust then mediates the relationship between product reviews and ratings as well as Shopee Live and purchase decisions. These findings highlight the importance of consumer trust in mediating the influence of e-commerce features on purchase decisions, as well as how interactive features such as Shopee Live can strengthen aspects of trust that ultimately influence consumer purchase decisions. With these findings, this research contributes to the development of digital marketing strategies on e-commerce platforms, especially in strengthening elements that can increase consumer trust, such as product reviews, ratings, and direct interactions through the Shopee Live feature. Sellers on Shopee are advised to pay more attention to the quality of product reviews and ratings and use Shopee Live as a means to build stronger consumer trust and drive higher purchase decisions.